Wednesday

July 23, 2014

July 23, 2014

Posted by **JASLEEN** on Wednesday, June 6, 2012 at 3:23am.

- MATHS -
**Reiny**, Wednesday, June 6, 2012 at 8:59amif x=-1, then -a + 3 + b - 6 = 0

a - b = -3

if x=-2, then -8a + 12 + 2b - 6 = 0

8a - 2b = 6

4a - b = 3

subtract them:

3a = 6

a = 2

in a-b=-3

2-b = -3

b = 5

so expression is

2x^3 + 3x^2 - 5x - 6

which is (x+1)(x+2)( ?x + ?)

by common sense, the last bracket must be

(2x -3)

so the third root is x=3/2

check:

(x+1)(x+2)(2x-3)

= (x^2 + 3x + 2)(2x-3)

= 2x^3 - 3x^2 + 6x^2 - 9x + 4x - 6

= 2x^3 + 3x^2 - 5x - 6 , all is good

**Related Questions**

Math - Q.1)If one zero of the polynomial 3x2-kx-2 is 2 find the other zero.allso...

Pre Calculus - 1. Find all rational zeros of the polynomial. Then determine any ...

calculus-can someone please help me with this ques - Find all zeros of the ...

Algebra - Can someone please explain how to do these problems. 1)write a ...

Algebra - Consider the polynomial: f(x) = 2x^3 – 3x^2 – 8x – 3. (a) By using the...

Math - Consider the polynomial f(x) = 2x^3 – 3x^2 – 8x – 3. (a) By using the ...

Algebra - Consider the polynomial f(x) = 3x3 – 2x2 – 7x – 2. (a) By using the ...

algebra - Consider the polynomial f(x) = 3x3 – 2x2 – 7x – 2. (a) By using the ...

algebra - Consider the polynomial f(x) = 3x3 – 2x2 – 7x – 2. (a) By using the ...

math - If the digits of a number may be any one of 0 through 9 (except the first...